O projeto de conservação e de restauro como elemento estruturador de programas de gestão do patrimônio construído: alguns estudos de casos entre o Brasil e a Itália alguns estudos de casos entre o Brasil e a Itália - Mario Fundaro (2018)
This thesis discusses the issues related to architectural restoration in its theoretical and practical aspects, focusing on Restoration Projects from a multidimensional perspective. That is, taking into account both the axiological, technological and architectural complexity involved in restorative action, as well as the necessary dialectics related to theory, applied regulations, professional training and regulation of the profession. The choice of the subject in question was not random, but was due to the increasing requirement, within the academic scope and the professional practice, of appropriate answers to concrete problems regarding Architectural Restoration. These answers are not yet clearly provided, in our view, by the Restoration theories, which have shown a certain inability to realise in practice the abstract concepts themselves. Therefore, the clear translation and application of theoretical constructs into pragmatic acts remains insufficient. The theoretical-methodological instrument that makes possible the effective concretization of this dialogue between theory and practice is, in our opinion, the Project. As such, it is treated in this thesis as a pivotal moment and indispensable in public policies to safeguard the historical built heritage. That said, must be noted that the paper is organized in three parts. The first part is dedicated to the incursion by the main theoretical lines of modern restoration, from a Technological Project perspective. We put Project practice at the centre of theoretical reflection, subverting some myths arising from certain criticisms of restoration. We continue with the same approach in the second part, by means of a critical comparison of the normative models in force regarding Restoration in Italy and Brazil; we investigated the diverse management of Restoration and Conservation Projects in the two countries. We later verified how these management models are reflected in the Project practice, through a comparative - and critical - analysis of six restoration interventions carried out in Brazil and Italy. The third part is reserved for the analysis of techniques used in Restoration Projects against rising damp and salt solutions, one of the most recurrent causes of pathologies in historic masonry. From this perspective, we present a wide compendium, largely unpublished in Brazil, of the most recent techniques developed by the restoration industry in this sector. In the development of this discussion, continuing in the comparative mode, we report concepts about materials and constructive systems in use in vernacular masonry - both in Italy and in Brazil. X. In the last part of the present research, we report the results of the experimentation, undertaken by us in two Brazilian historical buildings, of a technique to combat rising damp. In this way, we intend to bring new empirical data to the discussion, although still very incipient, that involves the Restoration Project, as well as the efficiency and possible negative impacts of imported conservative techniques without the appropriate contextualization, within the scope of safeguarding and conserving the built heritage in the Brazilian context.